Proposing Language Learning Material with Social Media towards Learning Beyond Classroom (LBC): Integrating TikTok for EFL Junior High School Students’ Speaking Material in Indonesia - Sucik Fitri Wulandari (Journal of Cultural Narratives in Digital Society, 2025)
In the digital era, social media platforms offer expansive opportunities for language learning beyond the traditional classroom. Among these, TikTok emerges as a dynamic tool that fosters authentic language use through short video creation and interactive engagement. Grounded in sociocultural theory and social constructivism, this paper explores the potential of TikTok as a Mobile-Assisted Language Learning (MALL) resource to support Learning Beyond the Classroom (LBC) for junior high EFL students. While existing studies acknowledge the positive influence of social media on English learning, limited attention has been given to the implementation of TikTok in fostering speaking skills outside formal learning environments. Addressing this gap, the study proposes a pedagogical framework integrating TikTok-based speaking materials, including a speaking worksheet and a detailed lesson plan aligned with the curriculum and learner context. The design aims to bridge in-class instruction with out-of-class practice, enhancing learner autonomy and communicative competence. The paper further discusses the theoretical underpinnings, design process, practical applications, and potential challenges of using TikTok for EFL instruction, offering actionable insights for language educators seeking to expand the scope of language learning beyond classroom boundaries.